MO081THE INFLUENCE OF VITAMIN D3 ON PODOCYTE DIFFERENTIATION IN SITU AND IN VITRO. (29th May 2021) - Lange, Tim; Kuhn, Laura; Böttcher, Marie-Christin; Simm, Stefan; Hammer, Elke; Kaderali, Lars; Völker, Uwe; Weber, Claudia; Endlich, Karlhans; Endlich, Nicole
Abstract: Background and Aims: Dedifferentiation of podocytes affects their complex 3 D morphology and is the main initiator for the development of chronic kidney disease (CKD). Unfortunately, there is no causal therapy for CKD until today. Thus, inadequate and late treatment lead to end-stage renal disease which subsequently makes renal replacement therapy inevitable. To address this, new treatment options are of high significance for CKD patients. Recently, vitamin D3 (VitD) became a promising candidate, but it is controversially discussed. In the present study, we investigated the influence of VitD on podocyte differentiation and the related pathways in situ and in vitro . Method: We combined a podocyte dedifferentiation model (Glom Assay ) with an automated imaging procedure ( Aquifer Imaging Machine ). We analyzed cultured glomeruli from transgenic mice expressing cyan-fluorescent protein (CFP) under the control of the nephrin promoter which were treated with VitD and its` analogue (calcipotriol). In this model, the decreasing CFP fluorescence is as a read out for podocyte (de)differentiation. Additionally, VitD-, calcipotriol- and VitD receptor (VDR) inhibitor (PS121912)-treated glomeruli were investigated by RNA-Seq and LC-MS/MS to reveal the molecular effects of VitD on podocyte differentiation. Furthermore, we treated cultured murine podocytes with VitD, calcipotriol and PS121912 to elucidate the morphological and molecular changes by immunofluorescence staining, RT-qPCR and Western blot. Results: VitD- and calcipotriol-treated glomeruli showed a significantly higher intensity of CFP fluorescence after 9 days, indicating higher level of nephrin compared to the control. This was verified by RT-qPCR and Western blot for nephrin and CFP. Additionally, we found an upregulation of VDR in VitD- and calcipotriol-treated glomeruli compared to controls. By transcriptomic and proteomic analysis, we identified molecular patterns that are specific for the different treated groups. Thus, we observed differential gene expression in VitD- and Wnt-signaling pathway as well as regulated genes that are essential for the actin cytoskeleton, focal adhesion formation and the slit membrane. Beside this, cultured podocytes showed a significant upregulation of the slit membrane protein nephrin, VDR and CYP24A1 by VitD. This is accompanied by an altered morphology of the podocytes due to a reorganization of the actin cytoskeleton. Conclusion: Our results show that VitD influences podocyte differentiation in situ and in vitro by the regulation of specific signaling pathways.